Francuski model ochrony sygnalistów a kształtowanie europejskich standardów ich ochrony - Lemonnier, Mariola (PRAWO i WIĘŹ, 2026)
The French whistleblower protection model is considered one of the most advanced and comprehensive systems in Europe. It is based on the Sapin II Act of 2016 and its 2022 amendment, introducing a flexible reporting procedure, broad protection against retaliation, a requirement for good faith, and legal and psychological support for whistleblowers. The model emphasizes confidentiality and data protection in line with GDPR requirements. It also takes a balanced approach to business secrecy, allowing for the disclosure of significant legal violations in the public interest. France played a key role in shaping the EU Directive 2019/1937, which incorporates many elements of the French system. Despite progress, practical challenges remain, such as low employee awareness and lengthy legal proceedings. The article highlights differences between the French and U.S. models and notes the trend of European whistleblower protection converging towards the French model, focusing on protection, support, and prevention of retaliation.